A multimodal logic for closeness. Issue 3 (2nd October 2017) - Burrieza, A.; Muñoz-Velasco, E.; Ojeda-Aciego, M.
Abstract: We introduce a multimodal logic for order of magnitude reasoning which considers a new logic-based alternative to the notion of closeness, we provide an axiom system and prove its soundness and completeness.